Prospects of Cage Fish Farming in South Western Uganda - Kwikiriza, Gerald; Mwesigwa, Tony; Barekye, Alex; Abaho, Ivan; Rwaheru Aheisibwe, Ambrose; Mwesige, Rose (Agriculture, Forestry and Fisheries, 2018)
The study was conducted to identify the constraints and potential opportunities of cage fish farming in South Western Highland Agro-Ecological Zone (SWHAEZ). 82 questionnaires were administered to six respondent groups (current cage fish farmers, potential adopters of cage aquaculture, farmers who have abandoned cage aquaculture, regional and district fisheries officers, and financial institutions) to obtain insight into the challenges in cage fish farming as well as opportunities that can be exploited to promote cage fish farming. People in relevant government institutions were also interviewed. Primary results show that lack of funds and lack of government extension services are key challenges in cage fish farming. Lack of funds incapacitates farmers’ failure to get aquaculture inputs like feed. It also accounted for the inability of potential adopters and farmers who have abandoned cage aquaculture to start or continue cage aquaculture respectively. Major opportunities identified include; availability of the market for the fish, willingness of the financial institutions to offer loans at a cheaper interest rate, availability of the extension services at the sub-county level. Our preliminary recommendations is that the government can also provide subsidies to most expensive inputs like feeds, seine-net, water testing kits and construction costs for aquaculture. There is need to empower and build capacity for the extension workers through improved good management practices like feed and feeding and record keeping.
Keywords: Tilapia; Cage Aquaculture; Adoption Constraints; Finance; Extension; SWHAEZ